DIRECTIONS FOR DEVELOPING THE INVESTMENT ACTIVITIES OF COMMERCIAL BANKS THROUGH THE STOCK MARKET (American Journal of Business Management, Economics and Banking, 2026)
This article examines the priority areas of development of investment activities of commercial banks through stock market instruments in modern economic conditions. The author analyzes the issues of increasing the share of securities in bank assets, diversifying the investment portfolio, and managing risks in the financial market. The article also studies foreign experience in strengthening the role of commercial banks as professional participants in the stock market, and develops scientific and practical proposals for the national banking system. The results of the research will serve to increase the profitability of banks and ensure their investment attractiveness.